2009
DOI: 10.1002/ejoc.200801300
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐ and pH‐Controlled Mechanized Nanoparticles

Abstract: A new class of mechanized silica nanoparticles, which exploits the stability of the inclusion complexes formed between ferrocenedicarboxylic acid and both cucurbit [7]uril (CB7) and β-cyclodextrin (β-CD), are described. Mesoporous silica nanoparticles, capable of storing a payload of small molecules and releasing it following particular activation processes, have been designed and decorated with ferrocenecarboxylic acid stalks. The storage and release of the payload is controlled by the host-guest interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 66 publications
(23 reference statements)
1
87
0
Order By: Relevance
“…[ 11 ] Zink et al demonstrated the pH-controlled release of guest molecules by employing iondipole interactions between curcubit [6]uril and bis-ammonium stalks [ 7b ] or by using the interaction between ferrocene derivatives and curcubit [7]uril. [ 12 ] A few acid-labile supramolecular nanovalves and gold nanoparticle-capped MSNs that regulate the release of cargo molecules have been reported. [ 6b , 7a , 11 ] Zhu et al reported that ZnO quantum dot lids on MSNs can be effi ciently dissolved in the acidic intracellular compartments of cancer cells, resulting in the release of the drugs from the pores of the MSNs into the cytosol.…”
Section: Doi: 101002/adma201201742mentioning
confidence: 99%
“…[ 11 ] Zink et al demonstrated the pH-controlled release of guest molecules by employing iondipole interactions between curcubit [6]uril and bis-ammonium stalks [ 7b ] or by using the interaction between ferrocene derivatives and curcubit [7]uril. [ 12 ] A few acid-labile supramolecular nanovalves and gold nanoparticle-capped MSNs that regulate the release of cargo molecules have been reported. [ 6b , 7a , 11 ] Zhu et al reported that ZnO quantum dot lids on MSNs can be effi ciently dissolved in the acidic intracellular compartments of cancer cells, resulting in the release of the drugs from the pores of the MSNs into the cytosol.…”
Section: Doi: 101002/adma201201742mentioning
confidence: 99%
“…(2) The modification of CBs is much more complicated and difficult than that of CDs. Zink,8–10 Kim,11, 12 and Feng13 have detailed work on functionalized inorganic nanoparticles with the surfaces wrapped with CDs as the gatekeepers. The supramolecular nanovalves for controlled release could be responsive to distinct external stimuli, such as pH, enzyme, light, and redox potential.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Zink and co-workers reported the design, synthesis and functional behaviour of a pH-controlled supramolecular gatelike scaffolding that consisted of a [2]pseudorotaxane formation through the encirclement of dialkylammonium cations with the macrocyclic polyether dibenzo [24]crown-8, [15,16] by using ion-dipole interactions between curcubit[6]uril and bis-ammonium stalks [17] or by using the interaction between ferrocene derivatives and curcubit [7]uril. [18] Kim and co-workers demonstrated the controlled release of guest molecules by employing a pH-responsive gating ensemble that used mesoporous materials based on a cyclodextrin/polyamine pseudorotaxane motif. [19] Other more sophisticated dual controlled release systems have been developed.…”
Section: Introductionmentioning
confidence: 99%